SURVEY OF SOME PLANTS IN NAINAMALAI FOOTHILL, EASTERN GHATS, NAMAKKAL - M, Sharmila; M, Rajeswari; Jayashree, Indhiramuthu; K, Tamizharasi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: This study was designed to document some medicinal plants in Nainamalai foothill. Methods: The plants were collected from different sites of the hill area, identified by their local names with the help of villagers while walking through the vegetation. The photographs of these plant species were taken during the field visits. Results: Plant survey at Ninamalai foothill has documented a total of 124 plants. Among 124 species surveyed, 123 were angiospermic plants and one pteridophytic plant. Analysis of plants showed that the more number of dicotyledons (115 species) belongs to 43 families and 8 monocotyledons are represented in 5 families. Within dicotyledons, 53 species are polypetalae, 34 species are gamopetalae, and 28 monochlamydeae. For each species, botanical name, family, habit, local name, parts used, and medicinal usage are identified and presented. The family-wise analysis showed that the family Amaranthaceae held the dominant position by representing more number of species (13 species). Habit-wise analysis shows that maximum representatives to the plants are from herb (76) community, followed by trees (22), shrubs (17), climbers (6), parasitic shrub and parasitic twinner (1), and fern (1). The absence of epiphytes indicates the loss special habitats due to the degraded status of the hill. Part-wise analysis showed the predominant use of whole plants, followed by leaves, root, seed, bark, fruit, flower, and stem. Conclusion: People of the study area mostly administered phytomedicine orally. A majority of remedies are prepared in the form of extract or juice, followed by powder form, decoction, and freshly collected plant parts. Most of the villagers in the study are poor, and they largely depend on plants for food, medicine, fuel, and other daily necessities.